The integration of Human Sciences and Revealed Knowledge in the KIRKHS - Hassan, Mohd. Kamal (IIUM Press, 2009)
Dr. AbdulHamid AbuSulayman, the second rector of the HUM, was never tired of emphasizing the need to reform the Muslim mind by integrating the revealed knowledge disciplines with the social sciences and the humanities, so that the disciplines and the scholars of those disciplines would be fully informed of, if not conversant with, the existing sociopolitical realities and the actual human conditions in all their diversities and complexities. Similarly, the human sciences would be infused with Islamic revealed values, perspectives and worldview in order to desecularize their contents and begin to enquire into the human condition from a holistic and taw~ldic perspective. These academic and intellectual reforms, he strongly believed, would go a long way towards ameliorating the miserable condition of the Muslim ummah throughout the world and reestablishing the holistic and balanced Islamic civilization that the Muslims once built with great flourish as universal centres of learning, innovation and enlightenment in West Asia, Spain (Andalusia) and India. The need to Islamicize the contemporary Western-inherited knowledge, particularly in the human sciences, and the need to make the revealed knowledge disciplines more realistic, relevant and contemporaneous - without altering the fundamental teachings and tenets of Islam - became the new intellectual focus of the HUM as it expanded with the establishment of the Kulliyyahs of Engineering, Medicine, Architecture and Environmental Design, Natural Sciences and Information and Communication Technology.....